Measuring efficiency of lean six sigma project implementation using data envelopment analysis at Nasa - David Meza; Ki-Young Jeong (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: This study aims to review the implementation of the Lean Six Sigma project methodology in the Johnson Space Center (JSC) business environment of National Aeronautics and Space Administration (NASA) with an objective of evaluating performance of individual projects and to develop recommendation for strategies to improve operational efficiencies based on Data Envelopment Analysis (DEA). Design/methodology/approach: In this study, authors propose the Lean Six Sigma project performance evaluation model (LSS-PPEM) based on Data DEA where Critical Success Factors (CSFs) and Total Team Hours serve as inputs while Process Sigma and Cost avoidance are used as outputs. The CSFs are factors that critically affect the performance of LSS at JSC. Six of those are identified by the Black Belts through Analytical Hierarchical Process, and the values of those are decided by project leaders and Green Belts through survey. Eighteen LSS projects are evaluated, and their results are analyzed. Findings and Originality/value: Eventually, four out of the six CSFs are adopted for this study based upon Pearson correlation analysis, and those four include Project execution and follow up of results; Top management's commitment and participation; The use of data analysis with easily obtainable data; Attention given to both long and short term targets. Using data between the years 2009 and 2011, seven of the eighteen projects are found to be efficient. The benchmark analysis and slack analysis are conducted to provide further recommendation for JSC managers. Three out of those seven efficient projects are most frequently used as an efficient peer. Practical implications: Traditionally, DEA has been considered as a data-driven approach. In this study, authors incorporate the survey-based CSFs into the DEA frame. Since many organizations may have different CSFs, the framework presented in this study can be easily applied to other organizations. Originality/value: This study provides a DEA-based framework and case study of LSS project evaluation in the government sector, which is very unique application to author's best knowledge. The framework is unique in terms of its input factor selection and quantification procedures.
Keywords: 650; performance measurement; Data Envelopment Analysis; Lean Six Sigma; government sector